Effect of PACK Corneal Cross Linking on Resistant Bacterial Keratitis - Naeima Elzelitni; Salsabeel Alzaidi (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and objectives. Corneal ulcer is a potentially blinding corneal disease that is traditionally treated with effective anti-microbial and, at times, more intrusive methods like keratoplasty. The motivation behind this study is to perceive how effective PACK corneal collagen cross-linking is in resistant corneal ulcers. Collagen cross-connecting (CXL) with UV light-initiated riboflavin is a corneal surface methodology used to treat keratoconus and corneal ectasia. It has recently been introduced for the management of infectious keratitis, particularly ulcers resistant to antimicrobial therapy or associated with corneal melting, due to the known microbicidal and corneal stiffening effects of ultraviolet irradiation and photo activated riboflavin. Methods. Seven eyes of seven patients with corneal ulcers included in this prospective interventional study in which patients not responding to conventional antibiotic therapy in first 7days, were treated with CXL. The procedure was performed according to the accelerated protocol CXl. Results. The mean age of patients was 65.7 years old (57.4 male, 42.9 female), mean ulcer size (3.6+-1.88*3.7+-1.89). Preoperative medications were continued after CXL in all cases. Microbiological exams revealed Pseudomonas aeruginosa in two cultures, in 5 of 7 eyes, progression of corneal melting was halted and complete epithelialization occurred. With mean duration of (30.3+-18.2), two eyes not responding to pack cxl and keratoplasty was needed. Conclusion. CXL can be considered as a promising new treatment in the management of refractory non healing bacterial keratitis with superficial stromal infiltrate. Cite this article. Elzelitni N, Alzaidi S. Effect of PACK Corneal Cross Linking on Resistant Bacterial Keratitis. Alq J Med App Sci. 2022;5(2):538-544. https://doi.org/10.5281/zenodo.7327093